Performance of crisphead lettuce cultivars under protected environment in different times of production1 - Aires, Eduardo Santana [UNESP]; Aragão, Carlos Alberto; Marinho, Lígia Borges; Gomes, Ítala Laiane Silva; Oliveira, Antônio Bruno Nunes; Yuri, Jony Eishi (Universidade Federal de Viçosa, 2020)
The objective of this work was to evaluate the behavior of Crisphead lettuce as a function of production seasons under different forms of protected environment. Two experiments were carried out in the field at different times: September to December 2017 and June to August 2018, in a randomizaed blocks desing, in a 4 x 7 factorial scheme, the first one being production environments under shade nets: red screen, chromatinet® screen, black screen and full sun, and the second, lettuce cultivars: Winslow, Irene, Balsamo, Rafaela, Iron Wood, Great Lakes and Delícia. The harvest was carried out at forty-two days after transplanting, where the following variables were analyzed: stem length (cm), total production and commercial productivity (t ha-1). The data were submitted to analysis of variance, and a joint analysis was performed to analyze the treatments effect, then the means were compared by the Scott-Knott test, at 5% probability. The microclimate was altered in the shaded beds, which affected the cultivars development. The cultivation in protected environment provides higher productivity of Crisphead lettuce from September to December, at that time the cultivars Balsamo and Delicia were highlighted under chromatinet®. In the period of mild temperatures, a better performance was observed for cv. Balsamo in full sun.
Keywords: Lactuca sativa var. capitata; handling; screens shading